Towards understanding the cutting and fracture mechanism in Ceramic Matrix Composites. (August 2017) - Gavalda Diaz, O.; Axinte, D.A.
Abstract: Ceramic Matrix Composites (CMCs) are increasingly used for the manufacture of high-value parts for several industries such as the aerospace, nuclear and automotive. Nevertheless, their heterogenic, anisotropic and brittle nature make difficult to characterise the machining process and therefore, an in-depth understanding of the cutting mechanics is needed. In this regard, this paper aims to understand the different behaviours of CMCs while employing orthogonal cutting. The first part of this article proposes a novel theoretical approach to explain the different types of cutting behaviours (fracture and shear cutting) based on the inelastic and orthotropic properties of the CMC's by using a high imaging system and measuring the cutting forces. The second part aims to understand the cutting and fracture mechanism by developing for the first time a specific analytical model for each of the three main orthotropic orientations, defined by the three main relative fibre orientations respect to the feed direction, which are found in cutting of CMCs. This is approached by the calculation of the specific cutting energy needed to fracture the CMC's during cutting (energy release rate, G c ) using fracture mechanics and cutting theories. This analytical model has been successfully validated for a Carbon/Carbon composite with the experimental data obtained for the brittle cutting and by introducing the concept of a rising R-curve in cutting models. Moreover, comparing the results obtained for the energy release rate for the brittle and semi-ductile mode, it is observed that the material experiences an important change in the energy release rate according to the brittle-to-semi-ductile transition occurring while reducing the depth of cut. Finally, a novel monitoring method based on the vibrations of the sample has been found successful to understand the type of crack formation appearing while cutting CMCs. Abstract : Highlights: Cutting model for Ceramic Matrix Composites for the three orthotropic orientations. Experimental trials in a Carbon-Carbon showing different cutting behaviours. Frames from the high imaging system and vibration and force signals are presented. Results for the energy release rate in cutting have been presented.